Study of the Billings ovulation method for fertility regulation in Lombardy - Dedé, Achille (Medicina e Morale, 2024)
The Billings Ovulation method is based on the daily analysis of changes in cervical mucus secretion that every woman can verify by studying the sensation perceived in the vulva and observing the appearance and consistency of cervical mucus flowing from the genitals.